2013
DOI: 10.1109/jsee.2013.00015
|View full text |Cite
|
Sign up to set email alerts
|

Polytopic LPV modeling and gain-scheduled switching control for a flexible air-breathing hypersonic vehicle

Abstract: A novel gain-scheduled switching control method for the longitudinal motion of a flexible air-breathing hypersonic vehicle (FAHV) is proposed. Firstly, velocity and altitude are selected as scheduling variables, a polytopic linear parameter varying (LPV) model is developed to represent the complex nonlinear longitudinal dynamics of the FAHV. Secondly, based on the obtained polytopic LPV model, the flight envelope is divided into four smaller subregions, and four gain-scheduled controllers are designed for thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…59, No. 4,2016 where u 0 is a virtual control variable, the original system (7) can be appropriately reformulated as…”
Section: Attitude Control Designmentioning
confidence: 99%
See 1 more Smart Citation
“…59, No. 4,2016 where u 0 is a virtual control variable, the original system (7) can be appropriately reformulated as…”
Section: Attitude Control Designmentioning
confidence: 99%
“…[1][2][3][4] In addition to the precise attitude control requirement for hypersonic vehicles, an efficient path control is also necessary. For the longitudinal dynamics, it is well known that there are correlations between the pitch angle and flight path angle.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported a polytopic parameter-varying model applied to a flexible air-breathing hypersonic vehicle; they divided the system into sub-regions, proposed a controller for each sub-region and switched between them to get closed-loop asymptotically stable local systems. A similar approach applied to unmanned aerial vehicles was reported in [52], but in both cases, the polytopic subsystems were considered adjacent simplifying the stability analysis. The case of asynchronous polytopic switching was addressed on [53] for a highly maneuverable vehicle; in such paper only numerical simulations were reported.…”
Section: Introductionmentioning
confidence: 99%
“…For an AHV with actuator faults, an adaptive faulttolerant controller is devised on the basis of a TakagiSugeno (T-S) fuzzy system [11]. In [12,13], a linear parameter-varying (LPV) affine model is first constructed to describe the complex longitudinal dynamics of an AHV. Then, a nonfragile switching tracking control methodology is proposed [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In [12,13], a linear parameter-varying (LPV) affine model is first constructed to describe the complex longitudinal dynamics of an AHV. Then, a nonfragile switching tracking control methodology is proposed [12,13]. In [14], a compound control approachcombined trajectory linearization control (TLC) with active disturbance rejection control (ADRC) is presented for an AHV.…”
Section: Introductionmentioning
confidence: 99%